Modal Split Perceptions and Preferences for Public Funding - Helmer, Viola (Technische Universität Dortmund, 2025)
The modal split, an indicator which summarizes the intensity at which different modes are used in a given location (proportion of trips made), is becoming a widely used benchmark in public policy and regional goal-setting. Using data from a 2024 survey among 3,052 participants in Germany, this study looks at the modal split indicator from the perspective of laypersons. This indicator is often used to communicate local mobility goals with the public. We investigate whether people are able to guess the modal split distribution in their locale, which modal split would be ideal in their view, and how these perceptions influence opinions on public spending for transportation. We also examine whether showing examples of real modal splits to a random subset of participants influences accuracy or any of our other markers. Results indicate that participants have some trouble guessing modal split proportions, and that the examples did not significantly improve this. For example, only 17% of participants' guesses for the car share are within 5 percentage points of the real split. However, 85.6% of participants would like the share of car trips to be lower by on average 22.2 percentage points (mean perceived car share is 55.2%). Additionally, introducing people to the concept of the modal split without also giving real world reference points negatively influences the amount of public funds they would like to be assigned to sustainable transportation modes.
TRR 391 Working Paper; 10
Keywords: modal split; perception bias; mobility preferences; information treatment; public spending; policy communication; 310